Methods of Introducing Innovative Pedagogical Technologies in Education - qizi, Alisherova Dilshoda Azizxon (International Journal on Orange Technologies, 2023)
This article discusses innovative pedagogical technologies and their effective, step-by-step use in education, the importance of pedagogical technologies in the educational process.